2008
DOI: 10.1038/npp.2008.50
|View full text |Cite
|
Sign up to set email alerts
|

Differential Involvement of Glutamatergic Mechanisms in the Cognitive and Subjective Effects of Smoking

Abstract: There is growing preclinical evidence for the involvement of glutamate in the behavioral actions of nicotine. The aim of this study, was to investigate the role of N-methyl-D-aspartate (NMDA) receptors in the cognitive and subjective effects of smoking in humans. Sixty regular smokers took part in this double-blind placebo controlled study, that investigated the effect of the NMDA-antagonist memantine (40 mg) and the nicotinic-receptor antagonist mecamylamine (10 mg) on smoking-induced improvement in performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 63 publications
(83 reference statements)
4
30
0
Order By: Relevance
“…reduced euphoria following DCS, compared to increased euphoria in Kamboj et al 2011), possibly implicating glutamatergic regulation of affect under conditions of nicotine deprivation (cf. Jackson et al 2009;Nesic et al 2011). …”
Section: Subjective Effects Of Dcsmentioning
confidence: 96%
“…reduced euphoria following DCS, compared to increased euphoria in Kamboj et al 2011), possibly implicating glutamatergic regulation of affect under conditions of nicotine deprivation (cf. Jackson et al 2009;Nesic et al 2011). …”
Section: Subjective Effects Of Dcsmentioning
confidence: 96%
“…A recent meta-analysis concluded that memantine improved cognition and clinician’s global impression in patients with Alzheimer’s disease [60]. Although it is not clear whether memantine improves cognitive performance in healthy adults [61], memantine attenuated nicotine self-administration in rats [62] and decreased the subjective effects of cigarette smoking in adult smokers [63]. Another study found no effect of memantine on cognition or smoking behaviour [63].…”
Section: Potential Treatments For Nicotine Withdrawal-induced Cognmentioning
confidence: 99%
“…Although it is not clear whether memantine improves cognitive performance in healthy adults [61], memantine attenuated nicotine self-administration in rats [62] and decreased the subjective effects of cigarette smoking in adult smokers [63]. Another study found no effect of memantine on cognition or smoking behaviour [63]. There is also evidence that combined treatment of memantine and AChEIs may be more effective at reducing cognitive decline in Alzheimer’s patients [64].…”
Section: Potential Treatments For Nicotine Withdrawal-induced Cognmentioning
confidence: 99%
“…In rodents, MTEP has reliably been shown to decrease seeking of cocaine (Bäckström and Hyytiä 2006; Knackstedt et al 2013; Kumaresan et al 2009; Martin-Fardon et al 2009), alcohol (Sidhpura et al 2010), methamphetamine (Osborne and Olive 2008), and opioids (Brown et al 2012). Several small-scale clinical trials have found that memantine reduces the subjective effects of nicotine (Jackson et al 2009) and heroin (Comer and Sullivan 2007) and reduces withdrawal symptoms from both alcohol (Krupitsky et al 2007) and opioids (Bisaga et al 2001). However, a larger, placebo-controlled study indicated that memantine does not reduce drinking in alcohol-dependent patients (Evans et al 2007).…”
Section: Transitioning To Addiction: the Neurobiology Of Regulated Anmentioning
confidence: 99%